Deaf children with cochlear implants in Chile: A national analysis of health determinants and outcomes in the Latin American context. - Mario Bustos-Rubilar; Fiona Kyle; Merle Mahon (PLoS ONE)
Deafness from birth represents a critical challenge for children's communication, with substantial public health considerations. One intervention has been cochlear implants (CI) for children with severe to profound deafness. Since 2008, Chile has implemented regulations to provide a CI at an early age. However, wide variability exists in factors and expected outcomes without previous national studies. This study aimed to characterise deaf children with CI in Chile and evaluate the impact of CI on speech perception and production, social inclusion, and parental satisfaction. We conducted a prospective study using hospital clinical records and an online questionnaire with 107 deaf children under 15 who had received CIs from 2017 to 2019. We characterised factors and outcomes and investigated the relationship between demographic, audiological, and social determinants of health and outcomes, including communication at home, CAPII, SIR, Geers and Moog Scale, Social Inclusion, and Parental Satisfaction. Our study showed a national profile of deaf children with CI, representing 70% of those implanted from 2017 to 2019. CI beneficiaries lived in more developed boroughs (.54) compared to the national average (.37). Communication and speech perception outcomes varied and were concerning, yet more positive outcomes were presented for social inclusion and parental satisfaction. We found an association between the measured outcomes and children's age, a socio-economic factor, CI use and CI training. This novel national study supports integrating public services close to each beneficiary's borough to improve outcomes with the device. CI use and parental training might be crucial measures during rehabilitation treatment.